Trapping and Driving Individual Charged Micro-particles in Fluid with an Electrostatic Device - Xu, Jingjing; Lei, Zijing; Guo, Jingkun; Huang, Jie; Wang, Wei; Reibetanz, Uta; Xu, Shengyong (Nano-Micro Letters, 2016)
A variety of micro-tweezers techniques, such as optical tweezers, magnetic tweezers, and dielectrophoresis technique, have been applied intensively in precise characterization of micro/nanoparticles and bio-molecules. They have contributed remarkably in better understanding of working mechanisms of individual sub-cell organelles, proteins, and DNA. In this paper, we present a controllable electrostatic device embedded in a microchannel, which is capable of driving, trapping, and releasing charged micro-particles suspended in microfluid, demonstrating the basic concepts of electrostatic tweezers. Such a device is scalable to smaller size and offers an alternative to currently used micro-tweezers for application in sorting, selecting, manipulating, and analyzing individual micro/nanoparticles. Furthermore, the system offers the potential in being combined with dielectrophoresis and other techniques to create hybrid micro-manipulation systems.